2015
DOI: 10.1007/s00464-015-4638-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bariatric surgery on systemic and adipose tissue inflammation

Abstract: Our results show significant and rapid increases in subcutaneous adipose adiponectin as early as 2 weeks post-bariatric surgery demonstrating reduced inflammation and possibly reduced insulin resistance. Future studies are warranted in larger cohorts with additional measurements of insulin sensitivity and inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
36
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 24 publications
8
36
1
1
Order By: Relevance
“…TNFα concentrations at 2 weeks, 6 months, and/or 13 months after laparoscopic RYGB (LRYGB), were indistinguishable from pre-surgical/baseline levels in two independent studies [35, 39]. A third study of samples from subjects undergoing LRYGB showed TNFα significantly increased 3 months post-surgery compared to baseline, while recapitulating the other studies’ findings of no change in TNFα in comparison at 6 and 12 month post-surgery [36].…”
Section: The Impact Of Bariatric Surgery On Diabetogenic Inflammamentioning
confidence: 84%
See 1 more Smart Citation
“…TNFα concentrations at 2 weeks, 6 months, and/or 13 months after laparoscopic RYGB (LRYGB), were indistinguishable from pre-surgical/baseline levels in two independent studies [35, 39]. A third study of samples from subjects undergoing LRYGB showed TNFα significantly increased 3 months post-surgery compared to baseline, while recapitulating the other studies’ findings of no change in TNFα in comparison at 6 and 12 month post-surgery [36].…”
Section: The Impact Of Bariatric Surgery On Diabetogenic Inflammamentioning
confidence: 84%
“…Taken together, these data indicate that acute phase proteins change more predictably than TNFα, IL-6, or other cytokines measured (MCP-1, IL-8 etc. [39, 5860] following bariatric surgery (Figure 1). One exception to the variability in cytokine responses to bariatric surgery is adiponectin, a generally anti-inflammatory cytokine made by adipocytes, which uniformly increases post- surgery [36, 61].…”
Section: The Impact Of Bariatric Surgery On Diabetogenic Inflammamentioning
confidence: 99%
“…Even within three months of surgery the expression of genes involved in macrophage recruitment, as well as histological detection of ATM in adipose tissue, have exhibited reductions [46]. Correspondingly, gene expression of the insulin sensitizing adipokine, adiponection, increases during this time frame [47]. Paradoxically, however, while Xu et al [44] observed improvements at three months after surgery in circulating high-molecular weight adiponectin and 5′ adenosine monophosphate-activated protein kinase (AMPK) activation, along with reductions in malonyl-CoA and oxidative stress in subcutaneous adipose tissue, there were no changes in the expression of inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%
“…Sams et al [21] found a significant and rapid increase in subcutaneous adipose anti-inflammatory cytokines (e.g. adiponectin) by enzyme-linked immunosorbent assay already 2 weeks following RYGBP, potentially contributing to systemic inflammation reduction.…”
Section: Bs and Inflammationmentioning
confidence: 99%
“…On the contrary, systemic and adipose-tissue inflammation seems to decrease following bariatric procedures both at the biochemical and at the clinical level. These changes supposedly promote risk reduction in obesity-associated comorbid conditions including T2DM, cardiovascular diseases, infections, and cancer [20,21,22,23]. …”
Section: Bs and Inflammationmentioning
confidence: 99%